Homozygous single base deletion in TUSC3 causes intellectual disability with developmental delay in an Omani family. Issue 7 (5th May 2016) - Al‐Amri, Ahmed; Saegh, Abeer Al; Al‐Mamari, Watfa; El‐Asrag, Mohammed E.; Ivorra, Jose L.; Cardno, Alastair G.; Inglehearn, Chris F.; Clapcote, Steven J.; Ali, Manir
Abstract : Intellectual disability (ID) is the term used to describe a diverse group of neurological conditions with congenital or juvenile onset, characterized by an IQ score of less than 70 and difficulties associated with limitations in cognitive function and adaptive behavior. The condition can be inherited or caused by environmental factors. The genetic forms are heterogeneous, with mutations in over 500 known genes shown to cause the disorder. We report a consanguineous Omani family in which multiple individuals have ID and developmental delay together with some variably present features including short stature, microcephaly, moderate facial dysmorphism, and congenital malformations of the toes or hands. Homozygosity mapping combined with whole exome next generation sequencing identified a novel homozygous single base pair deletion in TUSC3, c.222delA, p.R74 fs. The mutation segregates with the disease phenotype in a recessive manner and is absent in 60, 706 unrelated individuals from various disease‐specific and population genetic studies. TUSC3 mutations have been previously identified as causing either syndromic or non‐syndromic ID in patients from France, Italy, Iran and Pakistan. This paper supports the previous clinical descriptions of the condition caused by TUSC3 mutations and describes the seventh family with mutations in this gene, thus contributing to the genetic spectrum of mutations. This is the first report of a family from the Arabian peninsula with this form of ID. © 2016 Wiley Periodicals, Inc.